A análise do impacto das decisões judiciais sobre os planos de saúde suplementar: a nova sistemática da Lei de Introdução às Normas do Direito Brasileiro (LINDB) - Cerqueira, Rafael Soares de (2019)
The right to health with the promulgation of the 1988 Constitution came to be considered a fundamental social right, being addressed in more depth in the dissertation only under the bias of supplementary health, although the mixed system was adopted in Brazil. The double protection granted to the beneficiary / user of the health insurance plans, both as a recipient of fundamental rights and as a consumer of such services, will be studied. It will also analyze the regulatory policies applicable to the sector, as well as the possibility of judicial control of administrative acts related to the matter, culminating in the analysis of excessive judicialization of such policies, as well as the harmful economic side effects caused by this practice. To understand and seek possible answers to the topic of economic impact caused by judicial decisions related to the issue of supplementary health, the theoretical theory of Richard Alan Posner, based on the general instruments brought by the science of economics and, in particular, provided by the Economic Analysis of Law (AED). Thus, based on this pragmatic and consequentialist bias, it will be possible to better understand the size of such impacts, already properly contextualized according to the new provisions contained in the Law of Introduction to Brazilian Law Norms (LINDB). The most widely used research source will be the doctrine, through works published on physical basis - books and articles published in journals. Files located on the Internet will serve as a subsidiary source, especially for jurisprudential, legislative, and foreign text searches. The exposition of the theme will be guided by deductive reasoning, starting from more general aspects to the more specific ones, bringing, in the course of the study, the concordant or discordant positions of the doctrine about the postures adopted. At the end of the dissertation, what is intended is precisely to demonstrate the technical feasibility of implementing and effectively using the AED, as a model to be adopted by the Judiciary when delivering its decisions, in order to maintain legal certainty in relations involving the beneficiaries / users and the health plan operators.